DEEP ELECTRICAL STRUCTURE OF THE NORTHERN CASCADIA (BRITISH COLUMBIA, CANADA) SUBDUCTION ZONE: IMPLICATIONS FOR THE DISTRIBUTION OF FLUIDS - Soyer W.; Unsworth M. (My University, 2006)
Long-period magnetotelluric data have used to image the deep electrical structure of the Cascadia subduction zone in British Columbia, Canada. Zones of elevated electrical conductivity were found in both the forearc and backarc regions and are interpreted as a consequence of the fluid release from subducting slab. A shallow zone of high conductivity beneath Vancouver Island is likely due to fluids that are trapped above the subducting plate. East of this structure is a conductive (~0.03 S/m) forearc mantle wedge that also exhibits low seismic velocities and may be serpentinized. A free fluid phase is required to account for this enhanced conductivity. Elevated conductivities are observed in the upper mantle throughout the backarc (~0.01 S/m) and strongly support the hypothesis of a shallow, convecting asthenosphere. This enhanced upper mantle conductivity can be explained by either hydrogen ion diffusion in olivine minerals, or by a few percent partial melting (<4%). © 2006 Geological Society of America.
Keywords: ASTHENOSPHERE; CASCADIA SUBDUCTION ZONE; ELECTRICAL CONDUCTIVITY; FLUIDS; MAGNETOTELLURIC SURVEYS